Behavioral Problems among School Going Adolescents in Eastern Development Region of Nepal - Kafle, Tara Kumari; Kafle, Tika Kumari; Mashreky, Saidur; Rimal, Hem Sagar; Sapkota, Durga; Pokhrel, Archana (Birat Journal of Health Sciences, 2019)
Introduction: The public health relevance of mental health conditions including behavioural problems in children and adolescents has been a growing concern over the past decades. There are negligible studies found in mental health domains of adolescents in developing countries; studies with regional or national coverage are lacking in Nepal. Therefore, present study has been designed to explore the magnitude and risk factors of behavioral disorders among adolescents. Objective: The objective of this study is to examine the prevalence of behavioral disorders and its determinants among school going adolescence in Eastern Development Region of Nepal. Methodology: The study adopts analytical cross-sectional design with sample size 1500 involving 11 to 17 year school going adolescents and carried out in Eastern Development Region of Nepal during August to December 2016. Multistage probability sampling technique was used to draw the sample and validated self-report SDQ was used to estimate the behavioral problems. Ethical approval was taken from ERB of Nepal Health Research Council. Written informed consent was taken from each participant before collecting the information. Collected information were entered using Epi Data software and processed to SPSS version 16 for analysis. Both bivariate and multivariate analysis were carried out. Results: The prevalence of total (overall) behavioral problem was found among 35.0 % adolescents. While classifying, 13.3% were suffering from emotional disorder, 11.20% from conduct problem, 7.2% from hyperactivity/inattention, 4.9% from peer relationship problem and 2.1% from prosocial activities. In multivariate analysis, female adolescents, adolescents of uneducated or less educated parents (less than 10+2), residing in mountain ecological belt and adolescents without parents (dead or separated) were found positively associated with behavioral disorders. Conclusion: Total behavioral problem was found among 35.0% adolescents. adolecents of less educated parents, female sex, Mountain ecological belt and those without parents were more vulnerable to behavioral problem. Therefore, parental care seems to be very much essential to reduce the behavioural problems among children.